2015
DOI: 10.1002/adma.201501676
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Beam Epitaxy‐Grown SnSe in the Rock‐Salt Structure: An Artificial Topological Crystalline Insulator Material

Abstract: SnSe fi lms thicker than 20 nm go back to the GeS structure. We checked the surface morphology of a 20 nm fi lm with STM to see how the transition from rock-salt to GeS structures takes place. As shown in Figure 4 d, there are islands distributed on the surface with the height of 11.3 Å, obviously in GeS structure. RHEED and ARPES results show that most part of the fi lm is still of rock-salt SnSe. With more SnSe deposited, the fi lm surface is gradually covered by the GeS-type islands. Therefore, above 20 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 34 publications
5
81
0
1
Order By: Relevance
“…This is because there are two times of band inversion in the BZ (thus no net inversion). This is similar to the 2D group IV-VI TCIs whose band inversions occur twice at or in the vicinity of the X and Y points [5]. Here we argue that the SOC induced band gaps have topological crystalline feature.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…This is because there are two times of band inversion in the BZ (thus no net inversion). This is similar to the 2D group IV-VI TCIs whose band inversions occur twice at or in the vicinity of the X and Y points [5]. Here we argue that the SOC induced band gaps have topological crystalline feature.…”
supporting
confidence: 77%
“…Topological crystalline insulators (TCIs), whose topology is protected by point or mirror symmetry, have been receiving tremendous interest in both fundamental condensed-matter physics and materials science [1][2][3][4][5][6][7]. They extend the domain of topological materials beyond the prototypical Z 2 topological insulators (TIs) [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, GIVMCs have been classified into two groups according to their chemical compositions: MX (SiC,89 SiS,90 GeS,91, 92 GeSe,93, 94, 95, 96 SnS,97, 98, 99 SnSe,100, 101, 102, 103, 104, 105, 106, 107, 108 SnTe,109, 110) and MX 2 (GeS 2 ,111 GeSe 2 ,112, 113, 114, 115 SnS 2 ,72, 116, 117, 118 SnSe 2 73, 119, 120, 121, 122, 123, 124, 125). In this part, some typical GIVMCs are presented in Table 1 .…”
Section: Crystal Structuresmentioning
confidence: 99%
“…They also observed that there is no relative binding energy difference between theΓ andM Dirac points. In addition, Wang et al 63 obtained the metastable rocksalt SnSe (111) films with the molecular beam epitaxy (MBE), and demonstrated that the epitaxial rocksalt SnSe is also a TCI through observing its (111) surface states. …”
mentioning
confidence: 99%